STUDI MECHANICAL PROPERTIES MATERIAL CARBON FIBER REINFORCED POLYMER PRODUK LOKAL - Bisma Keshava; Usman Wijaya (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Carbon fiber reinforced polymer (CFRP) is a material that can be used to strengthen building structures. This study aims to test two CFRP material types, CFRP-A and CFRP-B, for structural strengthening. CFRP-A is an imported product, while CFRP-B is a locally produced product with more than 40% domestic content. Using local materials in CFRP aims to reduce costs for strengthening building structures. In this study, structural strengthening of beam elements with CFRP-A and B was carried out, where there was an increase in the shear strength of the existing beam structure by 31.147% and 25.154%, respectively. In addition, flexural strength also increased from the existing beam structure, which was 35.431% and 21.515% for CFRP-A and CFRP-B, respectively. From the results of this study, it is clear that CFRP-A is superior for shear and flexural strengthening. However, CFRP-B, a local product with a difference in shear strength increase from CFRP-A of 5.993% and at a relatively cheaper cost, can be considered for shear strengthening. Therefore, CFRP strengthening is an alternative to structural strengthening because it is easy to use, does not require much labor, and does not require many connections. Abstrak Carbon fiber reinforced polymer (CFRP) merupakan material yang dapat digunakan untuk memperkuat struktur bangunan. Penelitian ini bertujuan untuk menguji dua jenis material CFRP, yaitu CFRP-A dan CFRP-B, sebagai perkuatan struktural. CFRP-A adalah produk impor yang tersedia di pasar Indonesia, sedangkan CFRP-B merupakan produk yang diproduksi secara lokal dengan tingkat kandungan dalam negeri lebih dari 40%. Penggunaan bahan lokal dalam CFRP bertujuan untuk mengurangi biaya dalam memperkuat struktur bangunan. Dalam penelitian ini, dilakukan perkuatan struktural pada elemen balok dengan CFRP-A dan B, dimana terjadi peningkatan kuat geser dari struktur balok existing masing-masing sebesar 31,147% dan 25,154%. Selain itu, kuat lentur juga meningkat dari struktur balok existing yaitu sebesar 35,431% dan 21,515% untuk CFRP-A dan CFRP-B. Dari hasil penelitian ini terlihat jelas bahwa CFRP-A lebih unggul untuk perkuatan geser dan lentur. Namun CFRP-B yang merupakan produk lokal dengan perbedaan peningkatan geser dari CFRP-A sebesar 5,993% dan dengan biaya yang relatif lebih murah, CFRP-B dapat dipertimbangkan untuk perkuatan geser. Oleh karena itu, secara keseluruhan perkuatan CFRP dapat dipertimbangkan sebagai alternatif perkuatan struktur karena mudah digunakan, tidak membutuhkan tenaga kerja yang banyak, dan tidak memerlukan banyak sambungan.